Un Wanderer insolite cherche son chemin - Arlette Kosch (Recherches Germaniques)
Among all the caricatures of the misadventures of the inhabitants of the fictional small town of Krähwinkel, one engraving by C.G.H. Geiβler (from 1825) particularly stands out because of its quality and the force of its expression: one inhabitant of that little town, laden with technical equipment, sets out on foot to take a walk in the Swiss mountains. Following the experts’ advice, he is carrying on his shoulder a signpost, because unfortunately, from the three possible meanings of the word Wegweiser (a guide, either human or printed, or a signpost) he has taken the wrong one. Behind the humour in the foreground of this caricature can be discerned not only literary banter but also structural and political criticisms that turn this strange wanderer into the personification of a possible change in the social paradigm.